Development of a Wireless Sensor Network for Distributed Measurement of Total Electric Field under HVDC Transmission Lines. (20th May 2014) - Cui, Yong; Lv, Jianxun; Yuan, Haiwen; Zhao, Luxing; Liu, Yingyi; Yang, Hao
Abstract : A wireless sensor network-based distributed measurement system is designed for collecting and monitoring the electric field under the high voltage direct current (HVDC) transmission lines. The proposed system architecture is composed of a group of wireless nodes connected with electric field sensors and a base station. The electric field sensor based on Gauss's law is elaborated and developed. For the design of wireless node, the ARM microprocessor and Zigbee radio frequency module are employed. The proposed system has been used in China's state grid HVDC test base and the in situ power transmission projects. Based on the experimental results, the proposed measurement system demonstrates that it can adapt to the complex electromagnetic environment under the transmission lines and can accomplish the accurate, flexible, and stable demands of the electric field measurement.